Public-private partnerships for sustainable development emergence, influence and legitimacy - Pattberg, Philipp (Cheltenham Edward Elgar, 2012)
The 2002 World Summit on Sustainable Development in Johannesburg is remembered mainly for the promotion of a novel form of global governance: the so-called 'partnerships for sustainable development'. This book provides a first authoritative assessment of partnerships for sustainable development, ten years after the Johannesburg Summit.
Includes bibliographical references and index
Keywords: Sustainable development -International cooperation